Applying Vroom-Jago model Decision-Making Model of Leadership by Principals in Catholic Schools - Rosalinda Hernandez; Sister Olivia Agbakoba; Alexandro Garcia; Federico Guerra (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
Abstract This study investigates Catholic school principals' decision-making processes and leadership styles in the United States. Using a mixed-methods approach, the research surveyed 150 principals and conducted in-depth interviews with twenty participants. Key findings reveal that 68% of principals favor a collaborative leadership style, though external factors like diocesan policies and financial constraints significantly impact their autonomy. More experienced principals (10+ years) showed a higher tendency for unilateral decisions in crises. The study recommends that Catholic school leadership training programs integrate organized frameworks that balance collaborative methods with proactive action. These findings can guide diocesan leadership development programs, ensuring principals have specialized training in participatory decision-making and hierarchical leadership frameworks. It also highlights the importance of supportive diocesan structures to facilitate effective decision-making. This research contributes to understanding educational leadership in faith-based institutions and offers practical insights for improving Catholic school administration. Keywords: Catholic schools, principals, leadership, Vroom-Jago model, decision-making model